Acoustical finishes in auditoria / Yasmin Omar Lian - Omar Lian, Yasmin (2001)
This dissertation was also carried out to determine the type finishes executed in auditoria. Boundary finishes in auditorium is necessary in ensuring an auditorium perform its functional and maintain its existing for as long as it can.lt is therefore important that finishes design should not only be technologically up-to-date, but last and withstand to the numerous changes in the way performance are being staged. A theatre has to be protected from ail external noise and must have mechanical plant designed so that the background noise level does not exceed certain criteria. Acoustics is more an art than a science. Designing spaces, particularly auditoria is a difficult process and needs a competence person. It is acoustical environment implied by design and choices of material. Some boundary finishes should be lined with sound - absorbing material while other on reflective surfaces. The focus on the Istana Budaya and Dewan Filharnomik KLCC were found to have good effects on different acoustical and some similar material for sound absorption and insulation. Istana Budaya is a multipurpose auditorium which concentrates on theatrics and vocal performances The Philharmonic KLCC is designed specifically for instrument and vocal performance such as orchestra performance.